Optimizing water-efficient agriculture: evaluating the sustainability of soil management and irrigation synergies using fuzzy extent analysis - Rishikesh Sharma; Srinivas Rallapalli; Joe Magner (Scientific Reports)
Abstract Sustainable agriculture demands the integration of optimized irrigation and soil tillage practices. Poor selection or mismatched combinations of these practices can lead to inefficient resource use, declining soil health, and reduced crop productivity. Despite extensive research on individual tillage and irrigation methods, limited studies explored their combined effects on multiple agricultural sustainability parameters. This gap underscores the need for a comprehensive assessment framework that can guide farmers and stakeholders in identifying optimal combinations for diverse agricultural objectives. This study employs a compounded fuzzy extent analysis to evaluate the cumulative impact of various soil tillage and irrigation methods on key agricultural parameters, including affordability, maximum yield, climate resilience, water usage, soil disruption, disease resistance, ease of operation, nutrient utilization, and crop diversification. The analysis compares individual practices and their combinations using comparative matrices to identify the most suitable options across all parameters. The fuzzy logic approach addresses data uncertainty by converting linguistic variables into triangular fuzzy numbers, enabling more accurate decision-making. The results indicate that Zero Tillage is the most effective tillage practice (score of 0.176), while Deficit Irrigation emerges as the most efficient irrigation method, scoring 0.144. The research suggests that integrating Zero-Tillage (ZT) with Deficit Irrigation (DI) is the most cost-effective agricultural practice. Additionally, combining No-Tillage (NT) with Surface Irrigation and Mulching (SIM) results in higher yields and improved water use efficiency. Furthermore, the synergy of No-Tillage (NT) and Drip Irrigation (DI) enhances crop resilience to climate change. These findings provide valuable insights for developing sustainable agricultural strategies that balance productivity, resource conservation, and environmental protection.